2010
DOI: 10.1016/j.cell.2010.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Function of Tau Mediates Amyloid-β Toxicity in Alzheimer's Disease Mouse Models

Abstract: Alzheimer's disease (AD) is characterized by amyloid-beta (Abeta) and tau deposition in brain. It has emerged that Abeta toxicity is tau dependent, although mechanistically this link remains unclear. Here, we show that tau, known as axonal protein, has a dendritic function in postsynaptic targeting of the Src kinase Fyn, a substrate of which is the NMDA receptor (NR). Missorting of tau in transgenic mice expressing truncated tau (Deltatau) and absence of tau in tau(-/-) mice both disrupt postsynaptic targeting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

87
1,795
4
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,598 publications
(1,933 citation statements)
references
References 67 publications
87
1,795
4
1
Order By: Relevance
“…6B and C). Similarly, ablation of the microtubule‐associated protein tau, which has been shown to reduce epileptic activity in a variety of seizure models,28, 30, 31, 32, 33, 34 tended to reduce interictal events by roughly 50% but, if anything, tended to slightly increase the left shift in spectral power in SYN mice (Fig. 6D and E).…”
Section: Resultsmentioning
confidence: 76%
“…6B and C). Similarly, ablation of the microtubule‐associated protein tau, which has been shown to reduce epileptic activity in a variety of seizure models,28, 30, 31, 32, 33, 34 tended to reduce interictal events by roughly 50% but, if anything, tended to slightly increase the left shift in spectral power in SYN mice (Fig. 6D and E).…”
Section: Resultsmentioning
confidence: 76%
“…The molecular basis for these alterations is unclear, but they are indicative of a redistribution of synaptic weights, which is consistent with the bidirectional effect of PSD size that we also observed in these neurons. In fact, Tau is present in dendritic spines (Ittner et al , 2010; Mondragon‐Rodriguez et al , 2012; Frandemiche et al , 2014). In these structures, it has been shown that activation of NMDA glutamate receptor triggers Tau phosphorylation, thus regulating the interaction of Tau with the actin cytoskeleton, PSD95, and Fyn kinase (Ittner et al , 2010; Mondragon‐Rodriguez et al , 2012; Frandemiche et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It plays key roles in the establishment of neuronal polarity and migration during embryonic development (Caceres & Kosik, 1990; Dawson et al , 2001; Sapir et al , 2012; Sayas et al , 2015), in axonal transport (Ballatore et al , 2007; Hernandez & Avila, 2010) and in intracellular trafficking (Hernandez & Avila, 2010). Under physiological conditions, Tau is located mainly in axonal microtubules (Hirokawa et al , 1996; Aronov et al , 2001), although increasing evidence supports its presence also in dendrites (Ittner et al , 2010) and dendritic spines (Ittner et al , 2010; Mondragon‐Rodriguez et al , 2012; Kimura et al , 2014). The affinity of Tau to bind microtubules is finely regulated, depending mainly on the selective expression of various isoforms and post‐translational modifications.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we observed hTau‐A152T‐dependent neuronal loss in the hippocampus, consistent with findings obtained by Decker and colleagues 74. Mechanisms to explore in future studies include potential effects of the A152T substitution on (1) hTau/Fyn interactions 75, which could contribute to NMDA receptor‐mediated neurotoxicity 74, (2) network hyperexcitability 50, 76, and (3) tau's Gly 155 –Gln 244 region, which is exposed on the surface of tau oligomers 77 and might mediate interactions between these assemblies and cellular targets.…”
Section: Discussionmentioning
confidence: 99%